2021
DOI: 10.3390/cancers13143450
|View full text |Cite
|
Sign up to set email alerts
|

Explainable Artificial Intelligence Reveals Novel Insight into Tumor Microenvironment Conditions Linked with Better Prognosis in Patients with Breast Cancer

Abstract: We investigated the data-driven relationship between immune cell composition in the tumor microenvironment (TME) and the ≥5-year survival rates of breast cancer patients using explainable artificial intelligence (XAI) models. We acquired TCGA breast invasive carcinoma data from the cbioPortal and retrieved immune cell composition estimates from bulk RNA sequencing data from TIMER2.0 based on EPIC, CIBERSORT, TIMER, and xCell computational methods. Novel insights derived from our XAI model showed that B cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 67 publications
0
17
0
1
Order By: Relevance
“…It is becoming imperative to apply AI models that are inherently interpretable, together with XAI methods to tally accurate predictions with a better understanding of the underlying reasoning of the AI approaches. The need for using XAI techniques to explain individual decisions of predictive models has only recently emerged [ 37 ]. The use of XAI in oncology is still in its infancy, and is not widely appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming imperative to apply AI models that are inherently interpretable, together with XAI methods to tally accurate predictions with a better understanding of the underlying reasoning of the AI approaches. The need for using XAI techniques to explain individual decisions of predictive models has only recently emerged [ 37 ]. The use of XAI in oncology is still in its infancy, and is not widely appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…They identified survival-predicting genes in a sizeable pan-cancer cohort ( 9 ). The data-driven relationship between immune cell composition in the tumor microenvironment (TME) and >=5-year survival in breast cancer patients was investigated using an interpretable artificial intelligence (XAI) model to accurately predict clinical outcomes, thereby designing innovative strategies to cure cancer ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) plays an important role in tumorigenesis and progression. Novel techniques in artificial intelligence (AI) can help determine areas of therapeutic need, enhance clinical trial interpretation, identify novel targets, and generate accurate predictions that are impossible with traditional statistical techniques ( 11 ).AI is used to assess TME, prognosis and the benefit of adjuvant chemotherapy in patients after radical gastric cancer surgery and is a valuable addition to the current TNM staging system ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we further found that ASB16-AS1 expression was associated to different levels of immune infiltration in cancer types through a variety of immune cell content assessment methods. Immune cell content evaluation has differences, and multiple evaluation methods are mutually verified to effectively judge the relationship between ASB16-AS1 and immune cell subtypes [ 34 , 35 ]. Many immune cell subtypes are believed to play an important regulatory role in the development and treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%